Case report: Condylar metastasis from hepatocellular carcinoma: An uncommon case report and literature review - Liu, Xiaojie; Liu, Yanshan; Sun, Jian; Li, Ningyi; Fan, Cunhui; Chen, Liqiang (Frontiers in Oncology, 2023)
Background Patients with hepatocellular carcinoma are often affected by metastases, but condylar metastasis is particularly rare. Case presentation A 51-year-old man with a history of hepatocellular carcinoma requested treatment for facial pain. Computed tomography indicated that the condylar bone has been destroyed and fractured. Pathology confirmed condylar metastasis from hepatocellular carcinoma. Complete metastasectomy and condylar reconstruction were performed to preserve his facial appearance. No local recurrence or distant metastasis was found at 8 months of follow-up. Conclusion The condyle can be a metastatic site of hepatocellular carcinoma, regardless of its rarity. Long-term comprehensive surveillance and follow-up are needed for patients with hepatocellular carcinoma. The presence of solitary mass does exclude the possibility of metastatic cancer for these patients, and postoperative imaging and pathological diagnosis are important to determine its origin. If patients’ physical condition permits, the mass can be completely excised, and the physiological function can be restored and reconstructed.